2014
DOI: 10.4028/www.scientific.net/amm.566.193
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour and Design of Steel Columns Subjected to Vehicle Impact

Abstract: The main objective of this study is to develop a simplified analytical approach to predict the critical velocity of vehicle impact on steel columns. This method utilizes the energy balance principle with a quasi-static approximation of the steel column response. Results of ABAQUS numerical simulations of the dynamic impact response of axially loaded steel columns under vehicle impact are used to validate the proposed method. To account for the effect of vehicle impact, a simplified numerical vehicle model has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…In this study, the damping effect is neglected because it has no clear influence on structural behaviour for the studied cases. This can be attributed to the short duration of the impact compared to the natural period of the structural system (Jones, 1997, Al-Thairy, 2012. …”
Section: Element Typesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the damping effect is neglected because it has no clear influence on structural behaviour for the studied cases. This can be attributed to the short duration of the impact compared to the natural period of the structural system (Jones, 1997, Al-Thairy, 2012. …”
Section: Element Typesmentioning
confidence: 99%
“…Several studies (Al-Thairy, 2012, Jones, 1997 have suggested different failure modes for steel members under impact loads including global plastic failure, tensile tearing failure and shear failure. For externally bonded CFRP strengthened steel elements under static load, six possible failure modes have been suggested by (Zhao and Zhang, 2007).…”
Section: Failure Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental study conducted by Zeinoddini et al [15] found that the level of damage of tested un-strengthened columns was dependent on the level of axial preload. Al-Thairy [16] undertook an extensive numerical parametric study using the commercial finite element code ABAQUS to develop a simplified analysis method for axially compressed un-strengthened steel columns subjected to transverse impact. It was found that the location of the plastic hinge was almost always close to the centre of the column and was not dependent of the impact position except for a very low level of axial compression (<25% design resistance).…”
Section: Introductionmentioning
confidence: 99%
“…The nonlinear spring is modelled to define the load-deformation behaviour of vehicle during impact simulation. The validation of spring-mass vehicle model is conducted by comparing maximum contact force-displacement results with vehicle full frontal impact tests data available in US National Highway Traffic Safety Administration (NHTSA, 2011) and previous FE analysis (Al-Thairy 2012). The contact forces of vehicle frontal crush tests are estimated by Al-Thairy (AlThairy 2012) using the proposed equations (Campbell 1974;Jiang et al 2004) and vehicle frontal crush data from NHTSA.…”
Section: Spring-mass System Vehicle Modelmentioning
confidence: 99%